2012
DOI: 10.1016/j.ydbio.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The embryonic development of the centipede Strigamia maritima

Abstract: The geophilomorph centipede Strigamia maritima is an emerging model for studies of development and evolution among the myriapods. A draft genome sequence has recently been completed, making it also an important reference for comparative genomics, and for studies of myriapod physiology more generally. Here we present the first detailed description of myriapod development using modern techniques. We describe a timeline for embryonic development, with a detailed staging system based on photographs of live eggs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(146 citation statements)
references
References 24 publications
4
142
0
Order By: Relevance
“…centipedes, temporal variation is linked to a switch between a mechanism that counts with a two segment periodicity to one which generates single segments 16 . Recently published work 51 suggests the terminal Tribolium segments may also switch from a pair-rule patterning mechanism to an unknown mechanism that generated single segments.…”
Section: Figure 3 | Segment Addition Throughout Germband Elongation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…centipedes, temporal variation is linked to a switch between a mechanism that counts with a two segment periodicity to one which generates single segments 16 . Recently published work 51 suggests the terminal Tribolium segments may also switch from a pair-rule patterning mechanism to an unknown mechanism that generated single segments.…”
Section: Figure 3 | Segment Addition Throughout Germband Elongation Inmentioning
confidence: 99%
“…Support for a clock includes a clear demonstration of molecular oscillations in the flour beetle, Trobolium casteneum 14 . However, species-specific rates of segment addition or variations in those rates are not wellcharacterized among arthropods, with a few exceptions 15,16 .…”
mentioning
confidence: 99%
“…1), in which it was shown that gastrulation takes place along a ventral gastral groove, without the formation of a cumulus (Mayer and Whitington, 2009). Therefore, although the existence of a cumulus in myriapods continues to be unresolved (Brena and Akam, 2011), currently the most parsimonious explanation is that the cumulus evolved after the chelicerate-mandibulate split. However, as a migrating cumulus has also been described in a horseshoe crab (a marine group of chelicerates) (Sekiguchi, 1973), it is likely that this mode of development evolved very early in the chelicerate lineage (Redkin et al, 2008).…”
Section: The Segment Addition Zone: Insights Into Segmentationmentioning
confidence: 99%
“…Indeed, it is clear that at hatching, a geophilomorph centipede is little more than an embryo without an egg shell, still brooded by the mother for an additional long period. In this animal, the rupture of the egg chorion does not represent a clear-cut change from an embryonic to a post-embryonic state [5,6]. These nonfeeding post-embryonic stages reside with the mother, who stays coiled around them in the brood chamber, a small cavity in the soil matrix.…”
Section: Introductionmentioning
confidence: 87%
“…This analysis follows up published work on the embryonic development of Strigamia maritima where we have defined, described and timed the several stages [6]. Following a rather traditional approach, in this paper I will use a moult, or more precisely an ecdysis, i.e.…”
Section: Introductionmentioning
confidence: 99%